Urban segregation of London social housing estates: Measuring access to the city and the question of regeneration - Utzig Lukas; Karimi Kayvan (Lodz University of Technology Press, 2023)
While London is currently experiencing an acute shortage in affordable housing, local authorities are selling existing council estates for private redevelopment. This practice is often explained with the notion of failure of certain buildings, such as the Robin Hood gardens estate which went on to be partly demolished in 2017. At the same time increasing evidence has been gathered, which shows that social, walkable streets and neighbourhood amenities are especially important to economically vulnerable groups as they provide the basis for local communities that act as social support networks through childcare, informal employment, or housing. However, it is often these groups that are most affected by segregation through the urban form of the neighbourhood and limited access to the wider city. Research into segregated communities by Legeby, among others, suggests that a simple regeneration of the buildings themselves does not tackle the underlying problem of social urban resource distribution. This research will investigate the relation of urban form to the potential of pedestrian activity and distribution of neighbourhood resources for four high-rise council housing estates in London. An innovative workflow combines space syntax measures with Gravity accessibility, including the access to amenities such as shops and restaurants via the street network. The findings suggest that access to the resources the city provides, including access to urban co-presence, is very unequally distributed between the four case studies. It is also shown to what degree some urban form is creating obstacles and how it can be measured and compared. Improving opportunities through urban form in the neighbourhood may be an alternative to demolition of the buildings. Quantifying these inequalities offers a more nuanced debate about social housing redevelopment and a pathway for sustainable improvement.
Keywords: segregation; space syntax; accessibility; social housing; regeneration; segregacja; składnia przestrzeni; dostępność; mieszkalnictwo socjalne; regeneracja